PENGEMBANGAN EKONOMI MASYARAKAT MELALUI PEMBERDAYAAN USAHA MIKRO KECIL DAN MENENGAH (Studi Di Hapesong Baru Kecamatan Batang Toru) - Makhrani Makhrani; Diana Sari Harahap; Abdul Latif Lubis (Bajang Institute, 2022)
The Micro, Small and Medium Enterprises (MSME) sector has an important role in encouraging Indonesia's economic growth. MSMEs contribute about 87% to a number of business entities in Indonesia and have an 85% share in employment. In a business, it is necessary to study the feasibility of the business. However, in reality, business owners only focus on income and business sustainability. That's why community development with the method of social assistance needs to be done to help solve the problems that are being faced. Community Development contains efforts to increase participation and a sense of belonging to the program being implemented. Empowerment refers to the ability of a person, especially a weak group, to have access to productive resources that enable them to increase their income and participate in the development process and decision making. The results of this study indicate that the economic potential in Batang Toru District is agriculture, fisheries, tourism, and MSMEs. Supporting factors in community development in the economic field include abundant natural and human resources. While the inhibiting factors are limited capital, facilities and infrastructure and low community participation